Tourette Syndrome, ADHD and Other Comorbidity - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Tourette syndrome (TS) and its associated conditions are reviewed from University College and the National Hospital for Neurology and Neurosurgery, London, UK.